Analysis of Word-Formation Errors (Affixation, Reduplication, and Compounding) among Foreign Speakers in The “Akun Rakidarei”Database as Recommendations for Level 2 Bipa Word Card Materials - Hilya Shabrina; Hendra Setiawan; Cut Nuraini (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
This study aims to describe the types of word-formation errors made by non-native speakers on the Rakidarei account and to recommend digital flashcards as a learning tool for Level 2 Indonesian for Non-Native Speakers (BIPA). This study employs a qualitative approach using a descriptive method. The research data consist of Indonesian words and phrases extracted from videos uploaded by the Rakidarei account on YouTube. Data collection techniques included observation, transcription, documentation, and note-taking. The data were analyzed through the stages of identification, classification, and interpretation of errors based on the categories of affixation, reduplication, and compounding. The results showed that affixation errors were the most prevalent type, followed by reduplication and compounding errors. These errors were influenced by a lack of understanding of the morphological rules of the Indonesian language as well as interference from the speakers’ first language. The results of the study showed that 36 word-formation errors were identified, consisting of 28 affixation errors (77.78%), 6 reduplication errors (16.67%), and 2 compounding errors (5.56%). Affixation errors were the most prevalent type of error. Based on the research findings, the results of this analysis can be used as a basis for developing recommendations for digital flashcard materials for Level 2 BIPA instruction. Keywords: error analysis, affixation, compounding, reduplication, BIPA.